Audit Firm Appointments, Audit Firm Alumni, and Audit Committee Independence* - Lennox, Clive S.; Park, Chul W. (Contemporary Accounting Research, 2007)
A company officer is an "alumnus" if he previously worked for an audit firm. Iyer, Bamber, and Barefield (1997) find that alumni have ties with their former audit firms and alumni are more inclined to provide economic benefits to former firms if they have stronger ties. If the alumnus is a senior corporate officer, the alumnus may benefit his former firm by recommending that the company appoint the firm as its auditor. However, the company's audit committee may be concerned that officer-auditor ties threaten audit quality. Therefore, an independent audit committee may not sanction the appointment of the officer's former firm. This study investigates (a) whether companies tend to appoint officers' former audit firms, and (b) whether independent audit committees mitigate this tendency. We document that companies appoint officers' former firms more often than they appoint alternative audit firms. However, companies are less likely to appoint officers' former firms if audit committees are more independent. This suggests that independent audit committees strengthen audit quality by deterring affiliations between audit firms and officers. © CAAA.